Differential Fault Attack on LEA - Jap, Dirmanto (2016)
LEA is a symmetric block cipher proposed in 2014. It uses ARX design and its main advantage is the possibility of a fast software implementation on common computing platforms. In this paper we propose a Differential Fault Analysis attack on LEA. By injecting random bit faults in the last round and in the penultimate round, we were able to recover the secret key by using 258 faulty encryptions in average. If the position of faults is known, then only 62 faulty encryptions are needed in order to recover the key which surpasses the results achieved so far.